Episodic deformation and reactions in mylonitic high-grade metamorphic granulites from Dronning Maud Land, Antarctica - Engvik, Ane K.; Mertens, Cornelia; Trepmann, Claudia A. (Elsevier, 2020)
Microfabrics of mylonitic orthopyroxene-bearing quartzofeldspatic granulites from central Dronning Maud Land, Antarctica, have been investigated to evaluate the deformation behaviour at lower crustal conditions. The microfabric is characterized by a fine-grained matrix of dispersed feldspar, quartz and orthopyroxene, which contains monophase elongate quartz and feldspar aggregates, so-called ribbons, and elongate monocrystalline orthopyroxene ribbon grains. The observed crystallographic preferred orientation (CPO) of orthopyroxene ribbon grains that contain clinopyroxene exsolution lamellae in (100) and kink bands in equidimensional porphyroclasts indicate (100)[001] dislocation glide. Fine-grained matrix orthopyroxene formed by deformation of porphyroclasts and growth in strain shadows during diffusional creep, indicating a separate stage of deformation and reaction. Although dislocation creep of coarse ribbon quartz is indicated by sutured grain boundaries at high angle to the ribbon boundary and few subgrains, the weak CPO is rather unspecific. Fine-grained matrix quartz shows no indication of dislocation creep. We suggest that epitactic growth during quartz-producing mineral reactions played a major role for ribbon formation during diffusional creep. Our study demonstrates the importance of episodic deformation and metamorphic reactions in lower continental crust with transient high stresses allowing for dislocation glide of orthopyroxene enclosed in a fine-grained polyphase matrix undergoing diffusional creep on long term. ISSN:0191-8141